Histological Analysis of Somatic Embryogenesis from Immature Zygotic Embryo of Wild Banana Musa acuminata ssp. malaccensis - Handayani, Tri; Martanti, Diyah; Prawestri, Apriliana Dyah; Tihurua, Eka Fatmawati; Maharijaya, Awang; Wahyu, Yudiwanti; Sobir; Witjaksono (Journal of Tropical Crop Science, 2024)
Somatic embryogenesis, a crucial plant regeneration method, has become indispensable for crop improvement, particularly for species reliant on somatic cell manipulation techniques. Optimization of this process necessitates an understanding of the developmental stages involved. This study investigates the histological aspects of somatic embryogenesis in Musa acuminata ssp. malaccensis derived from immature zygotic embryos. Through detailed histological analysis, we aimed to elucidate the morphological changes and cellular organization occurring during the various stages of somatic embryogenesis, from induction, culture proliferation, and somatic embryo development to plantlet conversion. The initial stages of embryogenesis, characterized by nodules, were primarily composed of meristematic cells with high cell division activity. These cells contained tetrad-like structures that could develop into distinct two- and four-celled proembryoids or proembryogenic aggregates. Our histo-anatomical analysis revealed that embryogenic cultures proliferated through multiple pathways simultaneously: somatic embryo budding, proembryo formation, and pro-embryonic mass formation from both internal and peripheral cells. At the stage of somatic embryo development, embryos with a well-defined protoderm layer, containing cells with prominent nuclei and dense cytoplasm, potentially regenerate into plantlets. Furthermore, histological examination revealed the presence of procambium within mature somatic embryos, which subsequently developed into the vascular system of the complete plantlet